1998
DOI: 10.1243/0954406981521321
|View full text |Cite
|
Sign up to set email alerts
|

A feature complexity index

Abstract: An index is presented for quantifying the geometric complexity of a three-dimensional solid model. This provides a measure by which components may be compared one with another in relation to their relative complexity. The index is alphanumeric and readily computable. Such an index can be of use in the field of feature recognition as a means to determine how efficiently one algorithm handles components of varying complexity compared to another such algorithm.The performance of the authors' own feature recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…A number of studies have suggested techniques to evaluate the complexity of injection-moulded shapes with respect to replication and demoulding (Little et al 1998;Rosen et al 1992).…”
Section: Designing Mouldable Microfluidic Structuresmentioning
confidence: 99%
“…A number of studies have suggested techniques to evaluate the complexity of injection-moulded shapes with respect to replication and demoulding (Little et al 1998;Rosen et al 1992).…”
Section: Designing Mouldable Microfluidic Structuresmentioning
confidence: 99%
“…Many empirical studies in the construction field reflect that project complexity would affect the project duration, cost, and quality (Gidado and Millar, 1992;Raymond, 1995;Walker and Sidwell, 1996;Chan and Kumaraswamy, 1997;Chan, 1998;Dissanayaka and Kumaraswamy, 1999;Tatikonda and Rosenthal, 2000;Nassar and Hegab, 2006). It is has been widely accepted that the project complexity should be objectively measured in order to provide continuous feedback to help control the process of project development (Baccarini, 1996;Little et al, 1997;Calinescu et al, 2000;Sinha et al, 2006;Nassar and Hegab, 2006;Leung, 2007).…”
Section: Literature Review On Complexity Measuresmentioning
confidence: 99%
“…Various researchers have recognised the importance of objectively measuring complexity, as an aid to addressing the cause of such engineering and management related problems [4,5,6]. Our first objective is to decide what complexity is.…”
Section: How To Define Complexitymentioning
confidence: 99%